Essays on product market competition : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Finance at Massey University, Palmerston North, New Zealand - Zang, Suxiang (Massey University, 2023)
Product market competition is a fundamental economic mechanism and a key topic in recent decades. In this thesis, we analyse competition measurement to improve the credibility of relevant analyses, and we study relation of firm market power with investor sentiment to fill the gap in current literature. Essay One and Essay Two investigate a typical measure of industry concentration, the Herfindahl-Hirschman index (HHI), which is widely used to gauge competition based on industrial organisation theories. To facilitate HHI application and improve its measuring accuracy, we review the existing HHI proxies and recommend two simple HHI measures. Our survey shows that the convenient but misleading Compustat HHI is most frequently employed by researchers, while Census HHI that contains the most complete market share information of US firms is less preferred mainly due to low publication frequency and narrow industry coverage. Other HHI proxies developed recently often require extra data with complicated computation and are only occasionally employed. Comparatively, the simple HHI measures we propose are strongly correlated with the comprehensive Census HHI and are available at high frequencies for wide industries. Further, compared with Compustat HHI, the simple HHI measures better approximate Census HHI in association with important firm characteristics, and lead to more similar results as Census HHI in empirical examinations. Essay Three explores the relation between market power and stock sensitivity to investor sentiment, on which previous studies basically keep silent. We show that firms with the weakest market power have the most susceptible returns to investor sentiment, and that return spreads between firms with high and low market power are significantly higher after optimistic sentiment than pessimistic sentiment. The return patterns across market power portfolios are more evident when sentiment is more extreme, and when sentiment later weakens than strengthens. Our baseline regressions usually show significantly positive relation between the high-minus-low market power portfolio returns and the preceding sentiment levels, which pulls through a set of robustness tests. Conclusively, our finding reveals a negative relation between market power and sentiment-driven misvaluation, consistent with the argument that market power insulates profits and reduces performance uncertainties.
Keywords: Product differentiation; Mathematical models; Corporations; Investor relations; Competition; 350202 Finance